2004
DOI: 10.1002/nau.20033
|View full text |Cite
|
Sign up to set email alerts
|

Oral Kohki Tea and its protective effect against in vitro ischemic damage to the bladder

Abstract: These data are consistent with the concept that Kohki Tea acts by protecting the bladder from cellular damage caused by hypoxia and the generation of free radicals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 34 publications
(36 reference statements)
0
5
0
Order By: Relevance
“…The probable role of the oxidative stress on the physiopathology of the bladder dysfunction remains controversial. Previous studies showed that an ischemic period in the bladder, which is subjected to an acute distention, was followed by a reperfusion period resulting in free radical production and these studies speculated about a probable association of the reperfusion period with the chronic infravesical obstruction 17 , 18 . In these reports, MDA, which is the end product of the lipid peroxidation caused by free radicals, was used as a marker of cell membrane damage and disruption.…”
Section: Discussionmentioning
confidence: 99%
“…The probable role of the oxidative stress on the physiopathology of the bladder dysfunction remains controversial. Previous studies showed that an ischemic period in the bladder, which is subjected to an acute distention, was followed by a reperfusion period resulting in free radical production and these studies speculated about a probable association of the reperfusion period with the chronic infravesical obstruction 17 , 18 . In these reports, MDA, which is the end product of the lipid peroxidation caused by free radicals, was used as a marker of cell membrane damage and disruption.…”
Section: Discussionmentioning
confidence: 99%
“…Zhao et al were the first investigators to suggest that a bladder submitted to acute distension would initially present a period of ischemia, followed by a period of reperfusion, which would lead to the generation of free radicals and tissue lesions (10). More recently, a study developed by Levin et al demonstrated a possible relationship between a period of ischemia followed by reperfusion and the etiology of the bladder dysfunction subsequent to a period of chronic infravesical obstruction (7). These authors formulated the hypothesis that a state of oxidative stress would be present in a situation of chronic obstruction and that this would lead to the formation of metabolic end products that would cause damage to the phospholipids of the lipid membrane of the muscle cells.…”
Section: Discussionmentioning
confidence: 99%
“…The tubes were centrifuged at 1000 x G for 5 min and the top layer was measured fluorometrically at 532 nm. Total quantification of proteins was done by means of the Micro BCA protein analyzer, and the results were expressed as nmoL MDA/mg protein (7). The MDA levels were described in relation to the total protein levels.…”
Section: Malondialdehyde (Mda)mentioning
confidence: 99%
“…[2][3][4][5][6] In published studies similar to PBOO, in situ models of ischemia/reperfusion (I/R) also induced the generation of free radicals, which resulted in significant damage to the cellular and subcellular membranes, especially those of the nerves and mitochondria. [7][8][9] The authors of previous studies have demonstrated that natural products with strong antioxidant properties, such as Kohki tea, 10,11 grapes 12,13 and pygeum africanum 14,15 have protective effects against the damage mediated by both PBOO and in vivo and models of I/R. In a recent study, we evaluated the efficacy of the administration of two popular antioxidant agents, coenzyme Q10 and alpha lipoic acid, as a treatment for obstructive bladder dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…The authors of previous studies have demonstrated that natural products with strong antioxidant properties, such as Kohki tea, 10,11 grapes 12,13 and pygeum africanum 14,15 have protective effects against the damage mediated by both PBOO and in vivo and models of I/R. In a recent study, we evaluated the efficacy of the administration of two popular antioxidant agents, coenzyme Q10 and alpha lipoic acid, as a treatment for obstructive bladder dysfunction 16 .…”
Section: Introductionmentioning
confidence: 99%